Leadership lessons for any occasion : stories of our mothers - Betof, Edward; Betof, Nila (ATD Press, 2018)
First Lessons, Lasting Insights Nearly all of us have stories of advice given by the mom or mother figure in our lives. Mom is our first teacher and coach. For those of us who become leaders, teachers, and coaches, her guidance has a special value. In Leadership Lessons for Any Occasion: Stories of Our Mothers, executive coaches and authors Ed and Nila Betof have collected stories from a wide range of leaders, teachers, coaches, and talent development professionals about how their mothers guided their paths to helping others lead resourceful, meaningful lives. Stories have unique power to give us perspective, engage us with the empathetic aspects of coaching and leading, and approach problems from a new angle. This book offers bite-size anecdotes about how a mother's wisdom shapes the lives of leaders, coaches, trainers, and each one of us. Explore these stories as a way to reconnect with your own mother's legacy--or as a source of insight to share with your mentees and learners. Refill your tank of self-reflection, or use this book as inspiration to encourage others to dive deep into their own past and rediscover how their earliest childhood lessons could continue to help them grow today.